2014
DOI: 10.5194/esurf-2-233-2014
|View full text |Cite
|
Sign up to set email alerts
|

Coastal vulnerability of a pinned, soft-cliff coastline, II: assessing the influence of sea walls on future morphology

Abstract: Abstract. Coastal defences have long been employed to halt or slow coastal erosion, and their impact on local sediment flux and ecology has been studied in detail through field research and numerical simulation. The nonlocal impact of a modified sediment flux regime on mesoscale erosion and accretion has received less attention. Morphological changes at this scale due to defending structures can be difficult to quantify or identify with field data. Engineering-scale numerical models, often applied to assess th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Although there are no active interventions protecting the studied coastline, engineering activities since the late 19th century, designed to protect several kilometers of the coastline 2-15 km to the west (updrift), have reduced the supply of littoral sediment along the studied coastline; beach widths have been observed to be declining or been lost along the length East Sussex coastline (7). Numerical modeling has demonstrated that shoreline interventions can result in significant nonlocal impact many kilometers downdrift from the protected sites (3,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are no active interventions protecting the studied coastline, engineering activities since the late 19th century, designed to protect several kilometers of the coastline 2-15 km to the west (updrift), have reduced the supply of littoral sediment along the studied coastline; beach widths have been observed to be declining or been lost along the length East Sussex coastline (7). Numerical modeling has demonstrated that shoreline interventions can result in significant nonlocal impact many kilometers downdrift from the protected sites (3,34).…”
Section: Discussionmentioning
confidence: 99%
“…Rising sea levels and increased storminess may lead to accelerated coastal erosion rates in the future, potentially increasing hazard exposure (2)(3)(4)(5). To accurately assess coastal hazards in the face of future climate and land-use changes, it is necessary to understand the dynamics of cliff erosion over length and time scales relevant to the processes that drive change.…”
mentioning
confidence: 99%
“…There is societal need to assess the rates, and the change of rates, at which cliffed coastlines will erode in the face of changing sea levels and wave climates that may result in more energetic coasts (Bray and Hooke, 1997;Trenhaile, 2010;Ashton et al, 2011;Barkwith et al, 2014). The lack of long-term records of cliff and shore-platform erosion rates is a key problem to address (Trenhaile, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, although sea‐level and wave height having equal footing in the Hackney et al . () model employed in this study, it is wave height that has the largest effect on coastal erosion (Figure ), suggesting that for studies focused over the meso‐scale (~100 years) more focus should be paid to changes in wave heights in future studies of coastal erosion, particularly in cliffed environments where energy delivery to the cliff foot is likely the key driver of coastal erosion (Hackney et al ., ; Barkwith et al ., , ).…”
Section: Discussionmentioning
confidence: 97%
“…These interactions may produce responses in landscape evolution which are difficult to constrain in the currently available suite of terrestrial LEMs, none of which explicitly represent coastal geomorphic processes. Although coastal evolution models (CEMs; Ashton et al ., ; Barkwith et al ., , b) exist which are capable of modelling the dynamic evolution of shorelines, the inclusion of coastal processes as a boundary condition to a terrestrial LEM would be a useful and timely addition to this area of landscape modelling.…”
Section: Introductionmentioning
confidence: 99%